Mathematics in the First Language: Improving the Numeracy Skills of Grade One Learners - Aurelio Jr., S. Gomez (Yayasan Sembilan Pemuda Indonesia, 2025)
This phenomenological research study aimed to explore the improvement of the numeracy skills of the grade one learners through the use of first language. The participants were composed of seventeen (14) informants. They had undergone individual in-depth interview. Based on their narrations, all of them experienced different teaching strategies to improve numeracy skills of learners. Findings revealed that participants experienced strenuous facilitation of necessary numeracy skills among grade one learners when first language of the so called mother tongue language was used, thus, teachers had to apply repeated delivery of instruction to ensure mastery of skills using first language as medium of instruction. Learners did not have the comprehensive understanding of the lesson to augment numeracy skill in grade one level, learners tend to become introverted and unsociable thus, unable to relate and communicate the skill. In this sense teachers have to redirect pedagogical strategies sticking to first language as medium of instruction. Innovative and inventive way of determining strategies has to be given a critical point in deliberately adopting constant practical work approaches so learners can fully engage with the competencies with respect to grade one Math contents.